Effect of Gamma Irradiation on Callus of Handeuleum (Graptophillum pictum L. Griff) Kalimantan and Papua Accession - Rosmala, Arrin; Sukma, Dewi; Khumaida, Nurul (Jurnal Hortikultura Indonesia, 2022)
Handeuleum (Graptophyllum pictum L.Griff) is a medicinal plant that is widely used as a traditional medicine for its healing properties, hence it should be developed as one of the leading Indonesian medicinal plants. The combination of tissue culture and gamma irradiation are two common methods to improve vegetatively-propagated cultivars. This experiment aims to determine the effect of gamma irradiation dose-rate on the callus culture of the two handeuleum accessions. Callus generated from proliferation were irradiated with gamma rays (0 Gy, 15 Gy, 25 Gy, and 35 Gy) and then grown on regeneration medium containing BAP (4.44 μM and 8.88 μM) and TDZ (4.44 μM and 8.88 μM). The result of the experiment shows that RD50 was at19.25 Gy. The interaction among the Papua accession, gamma irradiation dose-rate of 15 Gy, and regeneration media 4.44 μM BAP produced the highest weight of callus subculture 1 and 2. Irradiation dose-rate of 25 Gy on Kalimantan accession resulted in the highest relative fresh weight growth of irradiated callus. The treatment with a 25 Gy dose-rate produced brownish-white callus and produced the highest value of variability in the relative growth rate of irradiated callus. Keywords: accession, irradiation dose-rate, purple leaves, variability